2014
DOI: 10.1016/j.apm.2014.03.048
|View full text |Cite
|
Sign up to set email alerts
|

Solution for Eshelby’s elliptic inclusion with polynomials distribution of the eigenstrains in plane elasticity

Abstract: Keywords:Eshelby's elliptic inclusion Plane elasticity Polynomials distribution of eigenstrains Complex variable method Closed form solution a b s t r a c t This paper provides a closed form solution for the Eshelby's elliptic inclusion in plane elasticity with the polynomials distribution of the eigenstrains. The complex variable method and the conformal mapping technique are used. The continuity conditions for the traction and displacement along the interface in the physical plane are reduced to a similar co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Thus, in this section, we will apply the solutions to consider (24) It can be found from Eqs. (23) and (24) that the value of radial stress inside the inclusion is equal to the hoop stress at the same position, while they are not equal outside.…”
Section: A Representative Example: Polynomial Series Distributions Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in this section, we will apply the solutions to consider (24) It can be found from Eqs. (23) and (24) that the value of radial stress inside the inclusion is equal to the hoop stress at the same position, while they are not equal outside.…”
Section: A Representative Example: Polynomial Series Distributions Ofmentioning
confidence: 99%
“…These studies, which can be mainly categorized into homogenous and inhomogeneous inclusion problems, have largely released the assumptions existed in the pioneering works of Eshelby [1][2]. Besides elliptical and ellipsoid inclusions and uniform eigenstrains distributed in inclusions, the studies have considered line [3][4][5], polygonal (or polyhedral) [6][7][8][9][10][11] and even arbitrary-shaped [12][13][14][15][16][17][18] inclusions and also extended the eigenstrains to non-uniformity [19][20][21][22][23]. A comprehensive review work can be found in literature [24].…”
Section: Introductionmentioning
confidence: 99%